Demographic Change and Development : Looking at Challenges and Opportunities through a New Typology - Ahmed, S. Amer (World Bank, Washington, DC, 2016)
Demographic change can be a positive contributor to development at any stage of demographic transition. This paper revisits the literature on the determinants and economic impacts of demographic change, and presents a new global typology that classifies countries into four categories based on demographic characteristics and future development potential. In the first group are high-fertility, low-income countries that are lagging in many human development indicators. In the second group are mostly low- and lower-middle-income countries where fertility rates have started falling recently and where changes in age structure offer tremendous opportunity for growth in the near future. The third group comprises mostly upper-middle-income countries that experienced rapid fertility declines in the 1960s, and where working age people will be a shrinking share of the population in the coming decade. The last group is made up of mostly high-income countries that have some of the highest shares of elderly in the world, and below-replacement fertility rates since at least the 1980s. The typology helps identify development policy priorities for countries in different stages of demographic transition, and opportunities through globalization due to demographic differences between countries.